Heart Failure in Atrial Fibrillation Subtypes in Women and Men in the Tromsø Study - Hilde Espnes, MD; Tom Wilsgaard, PhD; Jocasta Ball, PhD; Maja-Lisa Løchen, MD, PhD; Inger Njølstad, MD, PhD; Renate B. Schnabel, MD, MSc; Eva Gerdts, MD, PhD; Ekaterina Sharashova, MD, PhD (JACC: Advances)
Background: Atrial fibrillation (AF) and heart failure (HF) often coexist and impact morbidity and mortality. There is limited knowledge on the association of AF subtypes with HF according to sex. Objectives: The purpose of this study was to explore sex-specific associations between AF subtypes and subsequent HF, identifying HF risk factors in participants with AF, and exploring the combined impact on mortality. Methods: 14,790 women and 13,181 men from the Tromsø Study were enrolled between 1994 and 2008 and followed for incident AF and HF through 2016. Cox regression was conducted to provide HRs and 95% CIs. Results: Those with AF had higher risk of subsequent HF in both sexes compared to those without AF. Women with permanent AF had higher relative risk of HF than men (HR: 10.52; 95% CI: 8.72-12.70, and HR: 7.65; 95% CI: 6.40-9.15, respectively). Risk factors for HF in participants with AF included smoking in all, higher diastolic blood pressure and hypertension in women, underweight, obesity, and low alcohol consumption in men. All-cause mortality was higher in women with both subtypes (paroxysmal/persistent: HR: 2.10; 95% CI: 1.78-2.48, permanent: HR: 1.40, 95% CI: 1.14-1.72) and in men with paroxysmal/persistent AF (HR: 1.66; 95% CI: 1.40-1.96). Subsequent HF increased risk of mortality in both sexes. Conclusions: All AF subtypes were associated with increased risk of HF. Smoking was a shared risk factor, while diastolic blood pressure and hypertension were specific to women, and underweight, obesity, and low alcohol intake were specific to men. Subsequent HF increased mortality risk in all.